2018
DOI: 10.1172/jci96121
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 epigenetically orchestrates smooth muscle cell plasticity in arterial disease

Abstract: Adult vascular smooth muscle cells (VSMCs) dedifferentiate in response to extracellular cues such as vascular damage and inflammation. Dedifferentiated VSMCs are proliferative, migratory, less contractile, and can contribute to vascular repair as well as to cardiovascular pathologies such as intimal hyperplasia/restenosis in coronary artery and arterial aneurysm. We here demonstrate the role of ubiquitin-like containing PHD and RING finger domains 1 (UHRF1) as an epigenetic master regulator of VSMC plasticity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 53 publications
2
60
0
Order By: Relevance
“…Here we found that while EZH2 (or EZH1) loss-of-function reduced, their gain-offunction increased Uhrf1 mRNA ( Figure 7B). Thus, we identified UHRF1 as a novel target of EZH1/2 functional regulation, a finding consistent with the recently reported positive role of UHRF1 in SMC proliferation/migration and injury-induced IH 30 .…”
Section: Angioplasty Induces H3k27me3 Substitution By H3k27ac At Uhrfsupporting
confidence: 91%
See 2 more Smart Citations
“…Here we found that while EZH2 (or EZH1) loss-of-function reduced, their gain-offunction increased Uhrf1 mRNA ( Figure 7B). Thus, we identified UHRF1 as a novel target of EZH1/2 functional regulation, a finding consistent with the recently reported positive role of UHRF1 in SMC proliferation/migration and injury-induced IH 30 .…”
Section: Angioplasty Induces H3k27me3 Substitution By H3k27ac At Uhrfsupporting
confidence: 91%
“…Further attracting our interest, ChIPseq signal for H3K27ac at Uhrf1 magnified after injury ( Figure 7A). Consistently, recent reports indicated that UHRF1 functionally associates with histone methylation and acetylation 29 , and its upregulation in injured arteries promotes SMC proliferation and IH 30 . Interestingly, Ezh2 and Uhrf1 were reported to be in the same gene network both promoting keratinocyte self-renewal 31 , yet their epigenomic relationship was not known.…”
Section: Angioplasty Induces H3k27me3 Substitution By H3k27ac At Uhrfsupporting
confidence: 80%
See 1 more Smart Citation
“…PRISM interacted with G9a histone methyltransferase and class I histone deacetylases to induce genes associated with the proliferative smooth muscle phenotype while repressing regulators of differentiation, including myocardin and GATA-6 in primary VSMCs [61]. H3K27me3 and H3K4me2 were reportedly involved in neointima formation by regulating Myh11, Acta2, Cnn1, and Sm22 or Vcam-1 expression [62,63].…”
Section: Histone Methylation In Atherosclerosis and Vascular Intimalmentioning
confidence: 99%
“…Additionally, miR-145 regulates ubiquitin-like containing PHD and RING finger domains 1 (UHRF1), which interacts with DNA methyltransferase 1 (DNMT1), suggesting an indirect link between miRNA modulation and DNA methylation [67]. DNMT1 was found to methylate miR-145 promoter realizing a negative feedback loop [66] Moreover, low levels of miR145 allow the transduction of UTRF1 which is activator of DNMT1 that in turn methylates miR145 promoter activating a negative feedback loop.…”
Section: Methylation At Ncrna Promoters and Its Consequences For Cvdsmentioning
confidence: 99%